Strengthening organs of the State Sanitary Inspection within the applicable legal system in the context of maintaining proper sanitary safety levels - Sienkiewicz, Małgorzata (The Opole Studies in Administration and Law, 2020)
The article contains an analysis of the tasks implemented by the State Sanitary Inspection in the area of public health. The main responsibility of the inspection is first of all to maintain the proper level of sanitary safety in the country. The implementation of this task determines the scope of competences of the State Sanitary Inspection and its internal structure, which were described in the present article. The State Sanitary Inspector is also a state authority within the structure of the state administration that performs tasks under the specific legal regime of the state of epidemics.